2010
DOI: 10.1029/2010gl042816
|View full text |Cite
|
Sign up to set email alerts
|

Sahel dust zone and synoptic background

Abstract: Present weather reports from synoptic station data from 1983 to 2008 are analyzed to establish the climatological existence of a zone of frequent dust events and high dust concentration over the Sahel. This zone, to be referred to as the “Sahel dust zone” (SDZ), is situated between 10°N and 16°N, and is most prevalent during the period between December and April, stretching almost over the entire North African continent from west to east. SDZ corresponds well to the convergence zone located to the north of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 17 publications
3
46
0
Order By: Relevance
“…The dust may than be transported towards the Atlantic Ocean and beyond. Klose et al (2010) show that about half of dust suspended over the Sahel may be linked to a pressure pattern typical of Harmattan surges: a low over the Arabian Peninsula and the Azores High expanding eastwards into the continent. The mass of dust emission associated with cyclones has not been estimated before.…”
Section: S Fiedler Et Al: Dust Emission Associated With Depressionsmentioning
confidence: 99%
“…The dust may than be transported towards the Atlantic Ocean and beyond. Klose et al (2010) show that about half of dust suspended over the Sahel may be linked to a pressure pattern typical of Harmattan surges: a low over the Arabian Peninsula and the Azores High expanding eastwards into the continent. The mass of dust emission associated with cyclones has not been estimated before.…”
Section: S Fiedler Et Al: Dust Emission Associated With Depressionsmentioning
confidence: 99%
“…Arbuszewski et al in a research entitled "Studying the Effect of Tropical Convergence Zone on Aerosols" have shown that air masses of dust are fully associated with the location of ITCZ [5]. Seasonal variation in the spatial distribution of aerosols over Africa and nearby oceans is related to the large-scale atmospheric circulation, which is manifested by seasonal changes in the position of the intertropical convergence zone [6] and subsequent variations in the location and intensity of circulation centers [7] [8] [9]. The ITCZ is characterized by the convergence of dry northeasterly trade winds blowing over the Sahara, the so-called Harmattan winds, and humid south easterly winds originating farther south over the tropical Atlantic Ocean [7].…”
Section: Introductionmentioning
confidence: 99%
“…In similar studies of other regions, Klose [26] found that the Sahel dust zone corresponds well to the convergence zone located to the north of the African monsoon trough. However, Fiedler et al [27] highlighted that depressions are abundant and associated with 55% of the annual amount of dust emissions over North African dust sources.…”
Section: Introductionmentioning
confidence: 79%